Modeling of interactive buckling in sandwich struts with functionally graded cores - Wadee, M. Ahmer; Völlmecke, Christina; Yiatros, Stylianos (My University, 2013)
An analytical pilot model for interactive buckling in sandwich struts with cores made from a functionally graded material based on total potential energy principles is presented. Using a Timoshenko beam approach, a system of nonlinear differential and integral equations is derived that predicts critical and secondary instabilities. These are validated against numerical simulations performed within the commercial finite-element package Abaqus. Good agreement is found, and this offers encouragement for more elaborate models to be devised that can account for face-core delamination—a feature where functionally graded materials are known to offer distinct advantages.
Keywords: Structural stability; Buckling; Postbuckling; Sandwich structures; Struts; Interactive buckling; Functionally graded materials; Sandwich structures